Primary care physicians’ experiences with case finding for practice-based care management - Freund, Tobias; Wensing, Michel; Geißler, Stefan; Peters-Klimm, Frank; Mahler, Cornelia; Szecsenyi, Joachim (The American journal of managed care, 2012)
Objective: The identification of patients most likely to benefit from care management programs case finding - is a crucial determinant of their effectiveness regarding improved health outcomes and reduced costs. Until now, research has mainly focused on claims data-based case finding. This study aimed to explore how primary care physicians (PCPs) select patients for practice-based care management and how risk prediction may complement their case finding. Study design: Qualitative study. Methods: We performed 12 semi-structured interviews with PCPs from 10 small- to middle-sized primary care practices in Germany. The interviews focused on their criteria for selecting patients as potential participants of an on-site care management program and how PCPs evaluate claims data-based risk prediction as a case finding tool. All interviews were transcribed verbatim. We performed qualitative content analysis using the ATLAS.ti software. Results:Three major categories emerged from the physicians interviewed: 1) the physicians’ interpretation of the program’s eligibility criteria, 2) physician-related criteria and 3) patient-related criteria. The physician-related criteria included “sympathy/aversion” and “knowing the patient”. Patient-related criteria concerned care sensitivity in terms of “willingness to participate”, “ability to participate” (e.g. sufficient language skills, cognitive status) and “manageable care needs”. PCPs believed that their case finding can be supported by additional information from claims-data based risk prediction. Conclusions:Case finding for care management programs in primary care may benefit from a structured approach combining clinical judgement by PCPs and claims-data based risk modelling. However, further research is needed to identify the optimal case finding strategy for practice-based care management.